Progress in the classification, optimization, activity, and application of antimicrobial peptides - Su, Zuheng; Yu, Huajun; Lv, Tingting; Chen, Qizhou; Luo, Hui; Zhang, Haitao (Frontiers in Microbiology, 2025)
Antimicrobial peptides (AMPs) come from various sources and exhibit unique antimicrobial properties. Their rapid action, effectiveness, and resistance to resistance development make them promising alternatives to combat antibiotic resistance. In addition to its excellent antibacterial properties, AMPs have superior immunomodulatory, antitumor, and antiviral activities. In recent years, the demand for AMPs has continued to increase in many fields, especially in the medical field, and the prospects are extensive. However, AMPs have the disadvantages of expensive development cost, higher hemolysis, short half-life, susceptibility to degradation by protein hydrolases, low bioavailability, toxic side effects, and other disadvantages, which seriously limit the wide application of AMPs. Therefore, fewer AMPs have been approved for marketing or are undergoing clinical trials. The review covers the period from 2001 to 2025 and provides a detailed discussion by searching databases such as Google Scholar and Web of Science. This paper reviews the progress of research on AMPs sources, structures, optimization strategies, biological activities, mechanisms of action, and applications. In general, the development approaches and the number of new AMPs have increased significantly. The improvement technologies for AMPs high hemolysis, poor stability, low bioavailability and high cost have increased significantly. The development cost of AMPs is still high, but many AMPs have been widely used in clinical, food, livestock, poultry, cosmetics and other fields. This article focuses on the commonly used optimization strategies and main activities of AMPs, aiming to effectively respond to challenges and provide a theoretical basis for expanding their application range.